Analisis Kualitas Kesehatan Melalui JAMKESMA Pada Rumah Sakit Umum Daerah (RSUD) Kabupaten Nganjuk - Pamungkas, Dody Candra Putra (Jurnal Administrasi Publik, 2015)
Abstract: The Analysis of Health Service Quality through JAMKESMAS at Local Public Hospital (RSUD) of Nganjuk Regency. Research was conducted to understand the analysis of health service quality through JAMKESMAS at Local Public Hospital (RSUD) of Nganjuk Regency. Various health service programs had been released by the government for the poor community and one of them was Jamkesmas (Jaminan Kesehatan Masyarakat). In favor of smooth implementation of Jamkesmas, RSUD and Dinas Kesehatan were playing significant role in providing health service to the community of Jamkesmas participant. The importance of health service to the poor community was underlined by the assumption that the poor community could receive better service and then more equal service might be provided to other layers community. Realizing this goal required the improvement of health service quality through Jamkesmas at RSUD of Nganjuk Regency. The service procedure of Jamkesmas program was started by distributing precisely the service cards to the poor community and then was followed by providing medical service which considered attributes such as smoothness, speed, and reasonability of service cost and funding to Jamkesmas program. Keywords: Jamkesmas, Health Service, Poor Community Abstrak: Analisis kualitas pelayanan kesehatan melalui JAMKESMAS pada Rumah Sakit Umum Daerah (RSUD) Kabupaten Nganjuk; atas dasar banyaknya program pelayanan kesehatan yang digencarkan oleh pemerintah bagi masyarakat termasuk bagi masyarakat miskin melalui Jamkesmas (Jaminan Kesehatan Masyarakat). Dalam mendukung pelaksanaan program Jamkesmas RSUD dan Dinas Kesehatan memiliki peranan penting untuk dapat memberikan pelayanan kesehatan bagi masyarakat peserta Jamkesmas. Pentingnya pelayanan kesehatan bagi masyarakat miskin dimaksudkan agar masyarakat miskin bisa memperoleh pelayanan sebaik-baiknya dan pelayanan yang adil kepada semua lapisan masyarakat. Untuk itu perlu adanya upaya peningkatan kualitas pelayanan kesehatan melalui Jamkesmas di RSUD Kabupaten Nganjuk. Prosedur pelayanan program Jamkesmas dimulai dari pendistribusian kartu yang harus tepat sasaran untuk masyarakat miskin, pelayanan medis meliputi kemudahan, kecepatan serta kewajaran biaya pelayanan sampai pendanaan program Jamkesmas. Kata kunci: Jamkesmas, Pelayanan Kesehatan, Masyarakat MiskinÂ